Medieval women religious, c. 800-c. 1500 new perspectives - Curran, Kimm; Burton, Janet (Studies in the history of medieval religion, 2023)
A multi-disciplinary re-evaluation of the role of women religious in the Middle Ages, both inside and outside the cloister.